Cartas das amigas telespectadoras: feminismo, sexualidades e mediações (1980-1983) - Bueno, Heitor Campos (2020)
The Brazilian feminist movements played important roles in building a more just, egalitarian and democratic society. It is proposed to analyze the circularity of themes that made up the struggle agenda of feminist movements between the passage of the 70s and 80s in Brazil, as well as their influences in the process people construction of the people. For this purpose, the collection of letters sent to the extinct television program TV Mulher with the contribution of the feminist periodical Mulherio and the Folha de São Paulo newspaper through its Supplement Woman were used as documentary sources. The circumscribed period of analysis comprises the years 1980 to 1983. The research returned to the mediation processes established between the missivist viewers, and the media when looking for evidence present in the narratives and speeches recorded in their letters. The relationship established between the presenter and clinical psychologist of TV Mulher Marta Suplicy was also observed in this study. It is considered that through these traces and mediations, with the uses and practices of the progressive discourses of Brazilian feminists, normative processes occurred with effects of liberalization that led to advances and achievements in the quality of life of Brazilians